Measurement of stress waves induced by laser pulse - Radziejewska, Joanna; Marczak, Jan; Rycyk, Antoni; Jach, Karol; Sarzyński, Antoni; Strzelec, Marek (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> This letter describes modelling and experimental results of low and high pressure shock waves (of the order of 100 and 1000 bar, respectively) induced by pulse laser radiation. Measurements were performed using piezoelectric polymer PVDF sensors. The results of numerical calculations and their comparison with an experiment have been posted. Measured and calculated results have been used in estimation of the temporary course of signals from a fibre VISAR interferometer which measured the movement velocity of steel plate driven by the analysed shock waves. Description is supplemented with results of magnitude measurements of surface plastic deformation and material microstructure of samples. Full Text: PDF References J. Wang, N.R. Sottos, R.L. Weaver, "Tensile and mixed-mode strength of a thin film-substrate interface under laser induced pulse loading", J. Mech. Phys. Solids 52, 999 (2004). CrossRef R. Ecault et al., "A study of composite material damage induced by laser shock waves", Composites A 53, 54 (2013). CrossRef K. Jach et al., Computer modeling of dynamic interactions of bodies using free point method, Wydawnictwo Naukowe PWN, Warszawa, (2000) (in Polish). D.H. Dolan, Foundations of VISAR analysis, SANDIA REPORT, SAND2006-1950 (2006). CrossRef